2011
DOI: 10.1007/s10433-011-0181-9
|View full text |Cite
|
Sign up to set email alerts
|

Personality and personal control make a difference for life satisfaction in the oldest-old: findings in a longitudinal population-based study of individuals 80 and older

Abstract: This study investigates life satisfaction in relation to impending death among the oldest-old using overall disease load, self-rated health, and personality as interacting covariates of level and change. We used data from a sample of 370 healthy individuals who completed the Life Satisfaction Index-Z at four measurement occasions during a 6-year period in the Swedish OCTO-Twin study of individuals aged 80 and older. Growth curve analyses showed a linear decrease in life satisfaction as individuals approached d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 37 publications
6
42
1
1
Order By: Relevance
“…Previous research has repeatedly shown that mortality-related descriptions often provide a more accurate description of late-life changes in a variety of different domains, including indicators of cognitive abilities and well-being (Bäckman & MacDonald, 2006;Berg, 1996;Berg et al, 2011;. Our results generally support these findings for self-esteem, a central facet of people s' self-regulation system.…”
Section: Relative Stability In Self-esteem In Old Age and Close To Deathsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous research has repeatedly shown that mortality-related descriptions often provide a more accurate description of late-life changes in a variety of different domains, including indicators of cognitive abilities and well-being (Bäckman & MacDonald, 2006;Berg, 1996;Berg et al, 2011;. Our results generally support these findings for self-esteem, a central facet of people s' self-regulation system.…”
Section: Relative Stability In Self-esteem In Old Age and Close To Deathsupporting
confidence: 85%
“…Evidence for precipitous proximate-to-death declines that are often considerably steeper than the typical age-related effects has primarily accumulated in cognitive ability domains (for overviews, see Bäckman & MacDonald, 2006;Berg, 1996;Small & Bäckman, 1999). However, there is an increasing body of research showing that many aspects of well-being also show steep end-of-life declines (Berg et al, 2011;Diehr et al, 2002;Mroczek & Spiro, 2005;Palgi et al, 2010). There is even initial evidence to suggest that terminal decline is a highly pervasive phenomenon that affects many different domains, including those often considered relatively stable across old and very old age (Gerstorf, Ram, et al, 2012).…”
Section: Self-esteem Trajectories At the End Of Lifementioning
confidence: 99%
“…However, it has been suggested that control and autonomy facilitate pursuit of an enjoyable and fulfilling life (Doyal & Gough, 1991; and that perceived control mediates the effects of health on life satisfaction (Berg, Hassing, Thorvaldsson, & Johansson, 2011;Devins, 2010;George, 2010). Examining these two dimensions as a pathway may offer further insight into how chronic disease affects QoL.…”
Section: Introductionmentioning
confidence: 95%
“…Although a number of recent longitudinal studies have examined health, well-being, and life satisfaction (Berg, Hassing, Thorvaldsson, & Johansson, 2011;Fiori & Jager, 2012;Gerstorf et al, 2010;Schilling, Wahl, & Wiegering, 2013;Wickrama, Mancini, Kwag, & Kwon, 2013), few longitudinal studies have examined predictors of successful aging.…”
mentioning
confidence: 99%